PENGARUH FAKTOR-FAKTOR PRODUKSI TERHADAP PENDAPATAN USAHATANI JAGUNG DI DESA SUNGAI RIAM KECAMATAN PELAIHARI KABUPATEN TANAH LAUT PROVINSI KALIMANTAN SELATAN - Zulipah Mahdalena (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2016)
This research aims to determine the technical organization of corn farming and to identify factors that affect the production of corn farming at Sungai Riam village of Tanah Laut.This research also used the survey method and observation techniques. Respondents were 36 people, which was conducted by the census. Analysis tool used in the multiple linier regression analysis. Results of multiple linier regression analysis showed that there is significant influence between independent variable on the corn farming income. F test results showed that the significant influence between independent variables with the same dependent variable (income). While the results of the T test , showed in one by one the factors that significantly influence against corn farming income is the seed (X2) , labor outside the family (X3), urea fertilizer (X4), KCl fertilizer (X5), /sp-36 fertilizer (X6) , manure (X7) and herbicides (X8). Which is not significant is area of land (X1).Determination coefficient (R2) of 0.927 which means that the variable that is used to explain the variation of dependent variables 92,7 % while the remaining 7.3 % is influenced by other variables.